2020
DOI: 10.1186/s12891-020-03521-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delayed hip replacement on postoperative hip function and quality of life in elderly patients with femoral neck fracture

Abstract: Background: For various reasons, some elderly patients with femoral neck fracture undergo delayed surgical treatment. There is little information about the effect of delayed treatment on postoperative hip function and quality of life. The aim of this study was to investigate the effect of delayed hip arthroplasty on hip function, quality of life, and satisfaction in patients with femoral neck fractures. Methods: Forty-seven patients with femoral neck fracture and hip replacement delayed over 21 days served as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Mortality significantly increased for patients receiving hip repair surgery >24 hours after admission compared with those operated on within 24 hours [11]. A surgical delay of >21 days had a significantly poorer hip function and QoL than an operation within 7 days of the fracture [12]. Moreover, delays in surgery are correlated with a longer length of hospitalization and a lower possibility of returning to independent living [13].…”
Section: Introductionmentioning
confidence: 99%
“…Mortality significantly increased for patients receiving hip repair surgery >24 hours after admission compared with those operated on within 24 hours [11]. A surgical delay of >21 days had a significantly poorer hip function and QoL than an operation within 7 days of the fracture [12]. Moreover, delays in surgery are correlated with a longer length of hospitalization and a lower possibility of returning to independent living [13].…”
Section: Introductionmentioning
confidence: 99%
“…This high morbidity and mortality rate is associated with some complications due to prolonged bed rest after surgery ( Kenyon-Smith et al, 2019 ). Complications may include heart failure, thromboembolism, pneumonia, pressure ulcers, wound healing disorders, and delirium ( Flikweert et al, 2018 ; Song et al, 2020 ). Another complication Biz et al (2020) reported was the failure of femoral fracture osteosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines, however, recommend early surgery, if possible, because several studies have demonstrated improved outcomes, with no documented adverse effect of operating within 48 h, especially in otherwise physiologically healthy patients [ [10] , [11] , [12] , [13] , [14] ]. On the contrary, several deleterious effects have been reported with delayed surgery including, but not limited to, prolonged length of stay [ [15] , [16] , [17] ], pressure ulcers [ 6 , 10 ], arrhythmias [ 16 ], poor postoperative hip function [ 18 ] and increased mortality [ 12 , 19 ]. However, it is equally important to note that impetuous surgery without proper pre-operative stabilization can also lead to adverse outcomes as most of these patients are elderly with multiple comorbidities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%